If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + x + 9 = 37 Reorder the terms: 12 + 9 + x = 37 Combine like terms: 12 + 9 = 21 21 + x = 37 Solving 21 + x = 37 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + x = 37 + -21 Combine like terms: 21 + -21 = 0 0 + x = 37 + -21 x = 37 + -21 Combine like terms: 37 + -21 = 16 x = 16 Simplifying x = 16
| x^2-6x-y^2+7=0 | | -98y^2-26=0 | | x+15+19=41 | | 40x+35y=720 | | 9aq^4-9an^4=0 | | 4y-(2y+2)=18 | | 21+20+x=70 | | 6/6-5/6 | | 49x^2-490x+697+16y^2+128y=0 | | k^3+20k^2+100k=0 | | 0.6x-0.6(5-x)=1.2 | | 2(x-10)+6(x-2)=48 | | 3ct^4-3cj^2=0 | | 4x(5+2)=22 | | -9=15+b-3 | | 1/200/30 | | 100=800b+5 | | 3-(-6)+(-7)+(-4)= | | 6(m+8)+2m=35-5m | | 20v^2-39vd+18d^2=0 | | log(d)=0.44 | | (s/14)=p | | 7+42x=21x+(13) | | 5x-3=-8x+10 | | -23u^2+34=-32u^2+32 | | 2-(-4)+(-7)= | | u=4(7n+35)+7(n+1) | | 3ln(x-1)=-3 | | -10+1+7x=37 | | 11-(x+9)=9x-8 | | 38+n=66 | | 2f^2+9f+6=0 |